An update of molecular pathology and shifting systems of classification in tumours of the female genital tract. Issue 6 (June 2020) - Almadani, Noorah; Thompson, Emily Frances; Tessier-Cloutier, Basile; Pors, Jennifer; Hoang, Lynn
Abstract: The decreasing costs of next generation sequencing technologies and greater acceptance of molecular and biologic findings into the pathology domain, have shifted our paradigms of classification for many gynecologic tumors. This review focuses on major molecular developments within the last 5 years in endometrial carcinoma, endocervical adenocarcinoma, vulvar squamous cell carcinoma and uterine sarcoma, and the emergence of molecular subgroups within each family of tumors.